2014
DOI: 10.12956/tjpd.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Munchausen Syndrome by Proxy; A Serious Child Abuse Form

Abstract: GİRİŞDünya Sağlık Örgütü, bir yetişkin tarafından bilerek veya bilmeyerek yapılan ve çocuğun sağlığını, fi ziksel ve psiko-sosyal gelişimini olumsuz yönde etkileyen davranışları çocuk istismarı olarak tanımlamaktadır (1). Munchausen by proxy sendromu (MBP) çocuk istismarının çok ağır ve özel bir şeklidir. Hastanene hastane dolaşarak hastalık öyküleri uyduran veya oluşturan, bu nedenle gereksiz ve çok sayıda medikal veya cerrahi girişimler uygulanan hastaların "Munchausen sendromu" olarak tanımlamasından sonra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…In other studies, the mean score of the scale was found to be higher in mothers under the age of 30 (19,28). On the other hand, in some studies, the scale scores of middle-aged mothers were found to be higher than others (5,29,30). In our study, the scale score also decreases as the number of children increases.…”
Section: Discussioncontrasting
confidence: 64%
“…In other studies, the mean score of the scale was found to be higher in mothers under the age of 30 (19,28). On the other hand, in some studies, the scale scores of middle-aged mothers were found to be higher than others (5,29,30). In our study, the scale score also decreases as the number of children increases.…”
Section: Discussioncontrasting
confidence: 64%
“…Its prevalence has been reported as 0.4/100,000 in children aged younger than 16 years, and as 2–2.8/100,000 in children younger than 1 year. On the other hand, mortality due to MSBP has been reported as 6% to 10% 2 . This study highlights the importance of MSBP as a rare form of child abuse that is often overlooked.…”
mentioning
confidence: 77%
“…A relationship cannot be established between the clinical findings and the course of the disease. The patients usually do not respond to treatment, or symptoms increase and recur even if they initially do so 2,4 . In MSBP, the perpetrator is often the child's mother.…”
mentioning
confidence: 99%
See 2 more Smart Citations